Fryns syndrome phenotype caused by chromosome microdeletions at 15q26.2 and 8p23.1. Issue 9 (1st September 2005) - Slavotinek, A; Lee, S S; Davis, R; Shrit, A; Leppig, K A; Rhim, J; Jasnosz, K; Albertson, D; Pinkel, D
Abstract : Background: Fryns syndrome (FS) is the commonest autosomal recessive syndrome in which congenital diaphragmatic hernia (CDH) is a cardinal feature. It has been estimated that 10% of patients with CDH have FS. The autosomal recessive inheritance in FS contrasts with the sporadic inheritance for the majority of patients with CDH and renders the correct diagnosis critical for accurate genetic counselling. The cause of FS is unknown. Methods: We have used array comparative genomic hybridisation (array CGH) to screen patients who have CDH and additional phenotypic anomalies consistent with FS for cryptic chromosome aberrations. Results: We present three probands who were previously diagnosed with FS who had submicroscopic chromosome deletions detected by array CGH after normal karyotyping with G-banded chromosome analysis. Two female infants were found to have microdeletions involving chromosome band 15q26.2 and one male had a deletion of chromosome band 8p23.1. Conclusions: We conclude that phenotypes similar to FS can be caused by submicroscopic chromosome deletions and that high resolution karyotyping, including array CGH if possible, should be performed prior to the diagnosis of FS to provide an accurate recurrence risk in patients with CDH and physical anomalies consistent with FS.